2021
DOI: 10.1007/s00701-021-05045-1
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality visualization in brain lesions: a prospective randomized controlled evaluation of its potential and current limitations in navigated microneurosurgery

Abstract: Background Augmented reality (AR) has the potential to support complex neurosurgical interventions by including visual information seamlessly. This study examines intraoperative visualization parameters and clinical impact of AR in brain tumor surgery. Methods Fifty-five intracranial lesions, operated either with AR-navigated microscope (n = 39) or conventional neuronavigation (n = 16) after randomization, have been included prospectively. Surgical resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 45 publications
0
61
0
Order By: Relevance
“…This review is based on 95 references . We identified the utility of VR in neurosurgery, beyond planning, in the areas of neurosurgery training [2,, neuronavigation [15,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51], robotic neurosurgery [8,[52][53][54][55], pain management [56][57][58][59][60][61][62][63][64][65][66], rehabilitation [67][68][69][70][71][72][73][74][75][76], and consent taking [77][78][79][80], as well as diagnostic tools [81]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This review is based on 95 references . We identified the utility of VR in neurosurgery, beyond planning, in the areas of neurosurgery training [2,, neuronavigation [15,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51], robotic neurosurgery [8,[52][53][54][55], pain management [56][57][58][59][60][61][62][63][64][65][66], rehabilitation [67][68][69][70][71][72][73][74][75][76], and consent taking [77][78][79][80], as well as diagnostic tools [81]…”
Section: Resultsmentioning
confidence: 99%
“…In a recent article, T. Fick et al [40] have shown that a stand-alone AR HMD can be used in lieu of conventional neuronavigation, with significant advantages, such as direct superimposition of images the patient, improved ergonomics, and diminishing attention shifts [40]. The main benefit of AR HMD visualization in brain tumor surgery is the integrated continuous display, allowing for pointer-less navigation [46]. Navigation view provides the highest usability, while blocking the operative field less frequently.…”
Section: Virtual Reality For Neuronavigationmentioning
confidence: 99%
See 1 more Smart Citation
“…AR in neurosurgery involves an overlay of the necessary information, such as CT/MRI imaging and functional information augmented onto the surgical eld as the main visual reference plane [9]. Thereby, AR can provide crucial information such as tumour boundaries and risky adjacent structures to reduce surgical risks, reduce intraoperative cognitive load and provide information for the entire surgical team [34,49,64,86]. Multiple factors have been reported to in uence the suitability of cases for AR and VR.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, VR is recently emerging as an outstanding tool with highly promising potential. [4][5][6][7] Focusing on the case presented in this video article, 1 the following points should be considered concerning the choice of the surgical approach. Several alternative approaches can be selected for the removal of this kind of meningioma: Most of these are discussed by the authors and visualized by means of VR with interesting educational value.…”
mentioning
confidence: 99%